Simulation Of Blood Flow Through Mechanical Heart Valve Using Ansys Fluid Structure Interaction - Chai, Jien Wei (Universiti Sains Malaysia, 2017)
A successful mechanical prosthetic heart valve design is the bileaflet valve, which has been implanted for the first time more than 20 years ago. A key feature of bileaflet valves is the geometry of the two leaflets, which can be very important in determining the flow field. The aim of this research is to observe the flow pattern of the blood through the heart valve with different leaflets curvatures. In addition, the structural analysis of the leaflets was investigated. The simulation is carried out using ANSYS Fluid Structural Interaction(FSI). Particle image velocimetry experiment will also be conducted to validate the simulation results. Finally, the results such as velocity contour and vorticity are compared, revealing great similarity in leaflet motion and flow fields between the numerical simulation and the experimental test. Also, in this study, the leaflets which curved inwards with greater degrees are found to be the best configuration as it allows the greatest blood flow dynamic. Moreover, the maximum von mises stress is found to be at the hinge region. These results will serve as a basis for valve design to improve the hemodynamic of the heart.